(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
This paper introduces a tool to discover key sectors of a national or regional economy whose shares should be adjusted to offer optimal economic development constrained by environmental protection. The suggested approach uses an appropriately structured input-output model to find the projected gradient of economic development and the projected antigradient of CO2 emissions. The former is measured as Gross Domestic Product (GDP), the latter, as energy consumption. A linear combination of the two, in a proportion corresponding to the relative importance of GDP and CO2 emissions, determines the direction of optimal economic restructuring. It provides the maximum weighted difference between an increase in the GDP and a decrease in CO2 emissions. The main components of the direction vector show the key sectors. One of the advantages of the suggested approach is its reliance on gross output, final product, and energy consumption only; it does not use the intermediate inputs in the calculations. The United States case study is considered as an example.